2023
DOI: 10.3390/educsci13020156
|View full text |Cite
|
Sign up to set email alerts
|

Helping Students Become Proficient Problem Solvers Part I: A Brief Review

Abstract: Understanding issues involved in expertise in physics problem solving is important for helping students become good problem solvers. In part 1 of this article, we summarize the research on problem solving relevant for physics education across three broad categories: knowledge organization, information processing and cognitive load, and metacognition and problem-solving heuristics. We also discuss specific strategies discussed in the literature for promoting the development of problem-solving skills in physics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 138 publications
0
8
0
1
Order By: Relevance
“…Some teachers also reported that there was too little time to use additional materials in subject lessons fully, due to time constraints and the volume of the course syllabus, which is the main focus during the lesson. It is known that subject content knowledge is, indeed, particularly important for delivering effective PS activities in class (Maries & Singh, 2023). It can be concluded that teachers should be provided with very targeted methodological help and training about how to explicitly apply PS and SRL skills in various school subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some teachers also reported that there was too little time to use additional materials in subject lessons fully, due to time constraints and the volume of the course syllabus, which is the main focus during the lesson. It is known that subject content knowledge is, indeed, particularly important for delivering effective PS activities in class (Maries & Singh, 2023). It can be concluded that teachers should be provided with very targeted methodological help and training about how to explicitly apply PS and SRL skills in various school subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of PS skills has been studied widely by the fields of psychology and education and there are various and rather different approaches to defining and researching PS skills (see Contente & Galvão, 2022;Maries & Singh, 2023;Wu & Molnár, 2022). A thorough understanding of PS skills is crucial, as they are listed among the crucial life skills (or transversal skills) that students have to acquire.…”
Section: Problem-solving Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better appreciate the learning value of analogies and metaphors starts, it is important to start by contextualising them within experiential learning especially because of the latter's emphasis on learner agency and experiential student-centred learning (Dewey, 1938;Kolb, 1984;Kolb, & Kolb, 2009;Otte 2016). As Maries and Singh (2023) explain, analogies prompt learners to actively relate new concepts to familiar knowledge, consistent with Dewey's emphasis on learning from experience. Analogies prompt learners to relate new concepts to familiar knowledge, consistent with Dewey's emphasis on experiential learning (Miettinen, 2000).…”
Section: The Pedagogical Utility Of Analogies and Metaphors In Teachi...mentioning
confidence: 94%